Social Problem-Solving Skills and Empathy Levels of Veterinary Clinicians in Turkiye - Ozen, Rahsan; Alan, Seda Cavus; Ozen, Abdullah (Kafkas Univ, Veteriner Fakultesi Dergisi, 2023)
This study aimed to investigate the impact of the social problem-solving skills and empathy capacity of veterinary clinicians on their professional practice and to identify the major influential factors involved. For this purpose, 454 veterinary clinicians were enrolled in an online survey. Data was collected by applying a personal information sheet, the Social Problem Solving Inventory-Revised scale, and the Basic Empathy Scale. There was a negative correlation between clinicians' social problem-solving skills and general empathy capacity (P<0.001; r=-0.153) and emotional empathy capacity (P<0.001; r=-0, 255); a positive correlation between social problem-solving skills and cognitive empathy capacity (P<0.01; r=0.131). The study results showed that female had a greater capacity for empathy (P<0.05). It was determined that the participants' general empathy capacity (P<0.05; r=-0.098) and emotional empathy capacity (P<0.05; r=-0.102) decreased with a longer career as a veterinary clinician. The question If you had the chance to choose, would you opt again for being a veterinarian? was responded to with a no by clinicians with high emotional empathy (P<0.01) and with a yes by clinician with high social problem-solving skills (P<0.05) As a result, it could be speculated that activities such as veterinary faculty curriculum development or in-service courses on the improvement of cognitive empathy capacity would contribute to enhancing the performance of veterinary clinicians in dealing with problems.
Keywords: Cognitive empathy; Emotional empathy; Social problem solving; Tiirkiye; Veterinarians